Myotubularin-related protein 7 inhibits insulin signaling in colorectal cancer - Weidner, Philip; Söhn, Michaela; Gutting, Tobias; Gaiser, Timo; Kienle, Peter; Ebert, Matthias; Burgermeister, Elke (OncoTarget, 2016)
Phosphoinositide (PIP) phosphatases such as myotubularins (MTMs) inhibit growth factor receptor signaling. However, the function of myotubularin-related protein 7 (MTMR7) in cancer is unknown. We show that MTMR7 protein was down-regulated with increasing tumor grade (G), size (T) and stage (UICC) in patients with colorectal cancer (CRC) (n=1786). The presence of MTMR7 in the stroma correlated with poor prognosis, whereas MTMR7 expression in the tumor was not predictive for patients’ survival. Insulin reduced MTMR7 protein levels in human CRC cell lines, and CRC patients with type 2 diabetes mellitus (T2DM) or loss of imprinting (LOI) of insulin-like growth factor 2 (IGF2) had an increased risk for MTMR7 loss. Mechanistically, MTMR7 lowered PIPs and inhibited insulin-mediated AKT-ERK1/2 signaling and proliferation in human CRC cell lines. MTMR7 provides a novel link between growth factor signaling and cancer, and may thus constitute a potential marker or drug target for human CRC.